PERSPEKTYWY ROZWOJU BANKÓW SPÓŁDZIELCZYCH W POLSCE W WARUNKACH INTEGRACJI I GLOBALIZACJI RYNKÓW FINANSOWYCH - Szembelańczyk, Jan (Wydział Prawa i Administracji UAM, 2004)
National markets, when opening, expose their local financial institutions to international competition. Economic agents encounter both opportunities and threats in the new circumstances. The relative weakness of cooperative banks in Poland stemming from the historical and structural background needs to be shortly overcome. Surprisingly, the performance o f these financial institutions in Poland over the last four years has proved more effective than that of commercial banks. For a number of complex reasons, the market share of Polish cooperative banks is significantly weaker than in most EU countries. However, their growth potential is much stronger. This opportunity can be used subject to a variety of conditions. Firstly, the new financial architecture is indispensable for local communities. Secondly, the financial drainage of local communities (i.e. deposit transfer to interbank money market) ought to be limited or even eliminated as soon as possible. Thirdly, an intense economic educational campaign needs to be developed with a view to pointing out the results of transferring wealth via commercial bank channels. Consequently, a comprehensive concept of organizational structure and business practice within cooperative banking groups (associations) must be established. This concept should be based upon the heterogeneous structure of local cooperative banks and subsidiary functions of higher level banks (so-called ‘association banks’) and an adequate contemporary institutional mission.
PROSPECTS OF POLISH COOPERATIVE BANKS IN FINANCIAL MARKET INTEGRATION AND GLOBALISATION CONDITIONS